Confocal Laser Endomicroscopy as a Guidance Tool for Transbronchial Lung Cryobiopsies in Interstitial Lung Disorder - Wijmans, Lizzy; Bonta, Peter I.; Rocha-Pinto, Rita; de Bruin, Daniel M.; Brinkman, Paul; Jonkers, René E.; Roelofs, Joris J.T.H.; Poletti, Venerino; Hetzel, Jürgen; Annema, Jouke T. (Respiration, 2019)
Background: Transbronchial cryobiopsy (TBCB) of the lung parenchyma is a minimally invasive alternative for surgical lung biopsy in interstitial lung disease (ILD) patients. Drawbacks are the nondiagnostic rate and complication risk of pneumothorax and bleeding. Fluoroscopy is the current guidance tool for TBCB, which is limited by 2D imaging and a radiation dose for the patient. Confocal laser endomicroscopy (CLE) is a high-resolution imaging technique that provides immediate feedback during bronchoscopy about the elastin fiber network of peripheral lung areas. Both the visceral pleura and fibrotic lung areas consist of elastin fibers and are therefore potentially detectable with CLE. Objectives: To investigate whether CLE is capable of (1) distinguishing fibrotic from normal alveolar areas and (2) identifying the pleura. Methods: In and ex vivo CLE imaging obtained during bronchoscopy was compared with histology of lung biopsies in 14 ILD patients. Results: CLE imaging of the alveolar compartment was feasible in all patients without adverse events. Based on CLE imaging, key characteristics that influence both diagnostic yield (dense fibrotic areas) and complication rate (pleura and subpleural space) were visualized. Conclusions: CLE seems a promising alternative to fluoroscopy as a guidance tool for TBCB procedures.